Estudo anatômico, microquímico e quantitativo das fibras de órgãos vegetativos de arecaceae I. Desmoncus polyacanthos Mart., Manicaria saccifera G. - Rocha, Carla G. Souza (Museu Paraense Emílio Goeldi, 2022)
This work is part of a comprehensive project that aims to study anatomically the vegetative organs of some species of Arecaceae, and to analyze microchemically and quantitatively the fibers of these organs. Among these species, Desmoncus polycanthos (Jacitara) and Manicaria saccifera Gaertn (bussú) were chosen. The material was collected at Mocambo Reserve, MPEG Zoobotanical Park and in Afuá-Pa, following the usual techniques in anatomy. D- polycanthos, amphistomatic, with hypodermis attached to the epidermal cells. Vascular bundles of the mesophyll surrounded by a parenchymatic sheath, containing within it triangular silica crystals. At the level of the central vein there is a reinforcement of fibers. Stem atactostele with the bundles involved by fibers. The leaf fibers are slightly wavy with rhombic to tapered ends, varying from 470 µm to 1620 µm in length. Stem fibers range from 540 - 4160 µm M. sacciofera, hypoestomatic, bundles dispersed in the mesophyll surrounded by a parenchymatic sheath. Leaf fibers range from 350 - 3129 µm in length and bract fibers range from 510 - 1760 µm.